MemoBox: A mechanical follow-the-leader system for minimally invasive surgery - Culmone, Costanza; Jager, David J.; Breedveld, Paul (Frontiers in Medical Technology, 2022)
With the increase in Natural Orifice Transluminal Endoscopic Surgery procedures, there is an increasing demand for surgical instruments with additional degrees of freedom, able to travel along tortuous pathways and guarantee dexterity and high accuracy without compromising the surrounding environment. The implementation of follow-the-leader motion in surgical instruments allows propagating the decided shape through its body and moving through curved paths avoiding sensitive areas. Due to the limited operational area and therefore the instrument size, the steerable shaft of these instruments is usually driven by cables that are externally actuated. However, a large number of degrees of freedom requires a great number of actuators, increasing the system complexity. Therefore, our goal was to design a new memory system able to impose a follow-the-leader motion to the steerable shaft of a medical instrument without using actuators. We present a memory mechanism to control and guide the cable displacements of a cable-driven shaft able to move along a multi-curved path. The memory mechanism is based on a programmable physical track with a mechanical interlocking system. The memory system, called MemoBox, was manufactured as a proof-of-concept demonstration model, measuring 70 mm × 64 mm × 6 mm with 11 programmable elements and featuring a minimum resolution of 1 mm. The prototype shows the ability to generate and shift complex 2D pathways in real-time controlled by the user.